In vitro photoprotection and antioxidant capacity of Sphagnum meridense extracts, a novel source of natural sunscreen from the mountains of Colombia (2015)
ABSTRACT: Excessive ultraviolet radiation can cause skin cancer and related health problems in humans. Traditionally, organic and inorganic sunscreens have been used to minimize these effects. Besides, some phenolic compounds present in plants play an important role as photoprotectors. Sphagnum meridense (L), found in Colombia, is continuously exposed to sunlight on high mountain ecosystems. In this work, we evaluated the potential of S. meridense extracts to be applied as UVA-UVB filter in cosmetic formulations and its antioxidant capacity. The mixture acetone-37 % hydrochloric acid (1 %, v/v) showed the best polyphenol content and UVA-UVB absorption coefficient. These extracts also exhibited promissory UVAPF values, UVA/UVB ratio, critical wavelength (λc) and antioxidant capacity in vitro, comparable to that of conventional sunscreens.